Megatrends 2000 sepuluh arah baru untuk tahun 1990-an John Naisbitt dan Patricia Aburdene ; alih bahasa, FX. Bidijanto - NAISBITT, John; Aburdene, Patricia; Budijanto, Fx (Binarupa, 1990)
293 hlm 24 cm